2005
DOI: 10.1103/physrevlett.95.186801
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Independent Effective Mass in a Valley-Degenerate Electron System

Abstract: In a generic spin-polarized Fermi liquid, the masses of spin-up and spin-down electrons are expected to be different and to depend on the degree of polarization. This expectation is not confirmed by the experiments on two-dimensional heterostructures. We consider a model of an N -fold degenerate electron gas. It is shown that in the large-N limit, the mass is enhanced via a polaronic mechanism of emission/absorption of virtual plasmons. As plasmons are classical collective excitations, the resulting mass does … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
42
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…In Fermi liquid theory, interacting particles can be treated as non-interacting quasi-particles with a renormalized effective mass (m * ) and spin susceptibility, χ * ∝ g * m * , where g * is the Lande g-factor. In the highly interacting, dilute regime (r s > ∼ 3), χ * and m * are typically enhanced compared to the band values and increase with increasing r s , as confirmed both theoretically [1][2][3][4][5][6][7][8] and experimentally. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Besides r s , the spin and/or valley degrees of freedom also play an important role in the re-normalization of m * and χ * since they modify the exchange interaction.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In Fermi liquid theory, interacting particles can be treated as non-interacting quasi-particles with a renormalized effective mass (m * ) and spin susceptibility, χ * ∝ g * m * , where g * is the Lande g-factor. In the highly interacting, dilute regime (r s > ∼ 3), χ * and m * are typically enhanced compared to the band values and increase with increasing r s , as confirmed both theoretically [1][2][3][4][5][6][7][8] and experimentally. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Besides r s , the spin and/or valley degrees of freedom also play an important role in the re-normalization of m * and χ * since they modify the exchange interaction.…”
mentioning
confidence: 64%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Besides r s , the spin and/or valley degrees of freedom also play an important role in the re-normalization of m * and χ * since they modify the exchange interaction. 5,6,17,[24][25][26][27] In particular, it was recently demonstrated that when a 2D electron system is fully spin and valley polarized, m * is suppressed compared to its band value. [24][25][26][27] This suppression was reproduced in subsequent, numerical theoretical work.…”
mentioning
confidence: 99%
“…This is reminiscent of the predictions of the RPA model [16], according to which for the majority subband m * has to be smaller and T D to be lower due to better screening.…”
Section: Introductionmentioning
confidence: 84%
“…On the other hand, from intuitive expectations based on the RPA result [16,33], interactions within the minority subband should renormalize the effective mass stronger than in the majority one. In contrast to the latter expectations, earlier experiments [10,34] reported that the effective mass extracted from the amplitude of Shubnikov-de Haas (SdH) oscillations in Si-MOSFETs does not depend on the spin polarization to within 4%-5% accuracy.…”
Section: Introductionmentioning
confidence: 94%
“…In the highly interacting dilute paramagnetic regime ͑3 Ͻ r s Ͻ 26͒, m ‫ء‬ is typically significantly enhanced compared to its band value m b and tends to increase with increasing r s . [4][5][6][7][8][9][10][11][12][13][14] A question of particular interest is the dependence of m ‫ء‬ on the 2D electrons' spin and valley degrees of freedom as these affect the exchange interaction. Recent measurements of m ‫ء‬ for 2D electrons confined to AlAs quantum wells ͑QWs͒ revealed that, when the 2DES is fully valley and spin polarized, m ‫ء‬ is suppressed down to values near or even slightly below m b .…”
Section: Introductionmentioning
confidence: 99%